Taxonomía de las muertes violentas suscitadas en el Ecuador - Cruz-Piza, Iyo; Crespo-Álava, Xiomara Belén; Llanos-Parco, María Ysabel; Pilamunga-Barrionuevo, Luis Enrique (IUSTITIA SOCIALIS, 2021)
Taxonomía de las muertes violentas suscitadas en el Ecuador